IMPROVING THE QUALITY OF LIFE, DIAGNOSIS, AND OPTIMIZATION OF TREATMENT FOR PATIENTS WITH COMBINED MAXILLOFACIAL INJURIES - Rizaev Jasur Alimjanovich; Isomov Miraskad Maksudovich (Modern American Journals, 2025)
Combined maxillofacial injuries are among the most complex forms of trauma, often affecting both hard and soft tissues of the facial region. These injuries can significantly impair essential functions such as speech, mastication, breathing, and facial aesthetics, leading to a reduced quality of life. This article examines current approaches to improving the diagnosis, treatment, and rehabilitation of patients suffering from combined maxillofacial trauma. Emphasis is placed on timely diagnosis using modern imaging techniques, the development of individualized treatment strategies, and multidisciplinary rehabilitation to restore function and aesthetics. The article also discusses the importance of psychological support and long-term follow-up care. By optimizing treatment protocols and enhancing the quality of care, healthcare providers can significantly improve the life outcomes for these patients.
Keywords: Maxillofacial trauma, combined injuries, facial surgery, quality of life, diagnosis, treatment optimization, rehabilitation, imaging, multidisciplinary care, trauma management.